2013
DOI: 10.1007/s00590-013-1387-7
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation for stiffness following total knee arthroplasty: when and how often to do it?

Abstract: Stiffness following total knee arthroplasty is a disabling complication. One of the management options of stiffness includes manipulation under anaesthesia, but no real consensus exist on appropriate timing of intervention, and the timing and results of the manipulation under anaesthesia (MUA) are under debate in the literature. Our aim was to determine the efficacy of single and multiple manipulations under anaesthesia following total knee arthroplasty and to determine the most appropriate timing for manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…2016), warfarin treatment (Desai et al. 2014), history of previous knee surgery (Plate et al. 2016, Newman et al.…”
mentioning
confidence: 99%
“…2016), warfarin treatment (Desai et al. 2014), history of previous knee surgery (Plate et al. 2016, Newman et al.…”
mentioning
confidence: 99%
“…5,7,19 The literature is mixed on the fate of knees that undergo manipulation, with revision rates after MUA being reported between 3.2 and 14%. [21][22][23][24][25] Few studies have evaluated the long-term outcomes and revision risk of undergoing a MUA. 24,25 The purpose of this study is to evaluate the long-term outcomes and survivorship of patients who required a MUA after primary TKA compared with a cohort of patients who did not undergo a MUA.…”
mentioning
confidence: 99%
“…There are several small studies that, similar to this study, have reported a low incidence of revision arthroplasty following MUA in the short term (►Table 2). 11,13,14 Most recently, Desai et al evaluated the outcomes of a cohort of patients who underwent MUA following a failed course of physical therapy (n ¼ 86 patients). 11 After a 1-year follow-up, they were three (3.5%) patients who required revision TKA for persistent knee stiffness, which they believe was most likely due to an oversized femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 Most recently, Desai et al evaluated the outcomes of a cohort of patients who underwent MUA following a failed course of physical therapy (n ¼ 86 patients). 11 After a 1-year follow-up, they were three (3.5%) patients who required revision TKA for persistent knee stiffness, which they believe was most likely due to an oversized femoral component. Similarly, Namba and Inacio evaluated the outcomes of a cohort of patients who required an MUA following their TKA (n ¼ 195 patients).…”
Section: Discussionmentioning
confidence: 99%